DESIGN AND IMPLEMENTATION OF ACTIVITY CLASSIFICATION AND STEPS COUNTER ALGORITHM IN WECARE: WEARABLES FOR CALORIE REPORT - Putri Fazriani, Dewinta
Health is the most important part of human life. Humans use technology that has develop rapidly to form healthy lifestyle. One of the technologies used is wearable devices such ad fitness tracker or smartwatch. Because the product is easy to use in carrying out daily activities, many people use the information provided by the technology to regulate their lifestyle. The information provided by the technology is like the number of calories burned and the number of footsteps. However, according to a study published in JAMA, fitness tracker users who experienced less weight loss than those who did not use it, ie less than 50% [1]. Possibly this happened because of an information error that was given to the user due to an error in detecting the activity carried out by the user. WECARE, Wearables for Calorie Report is here to answer these problems. WECARE in its use will be used in the hands and feet of users in carrying out daily activities and is equipped with applications on smartphones that make it easy to display information about calories burned. In this book, it is explained about the development of WECARE related to data processing, namely the activity classification algorithm that uses machine learning classifier, step counter algorithm, and calorie conversion algorithm that utilizes Metabolic Equivalent of Task (MET).